Differences in motor function and psychological factors across phenotypic patterns of freezing of gait in Parkinson’s disease - CHANG Song; CUI Xiao; HUANG Heqing (陆军军医大学学报)
Objective‍　‍To investigate the characteristic changes in motor function and psychological factors among Parkinson’s disease (PD) patients with different phenotypic patterns of freezing of gait (FOG), and to explore the trends in phenotypic heterogeneity of these features. Methods‍　‍A cross-sectional study was conducted on 17 PD patients without FOG (PD-NFOG) and 25 PD patients with FOG (PD-FOG) [including 13 cases of trembling-in-place (TP) and 12 cases of shuffling-with-small-steps (SS)]. Another 28 demographically matched (age, gender, education level and others) healthy individuals were recruited from community and served as healthy controls (HC). Motor function was assessed using quantitative gait analysis and clinical scales, including the unified Parkinson’s disease rating scale part Ⅲ (UPDRS-Ⅲ) and H&Y staging. Psychological evaluations were carried out with Hospital Anxiety and Depression Scale (HADS-A/HADS-D), Generalized Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9), Snaith-Hamilton Pleasure Scale (SHAPS), Reading the Mind in the Eyes Test (RMET), Montreal Cognitive Assessment (MoCA), and digital symbol substitution test (DSST). Results‍　‍① There were significant differences between the PD-FOG and PD-NFOG groups in terms of motor parameters (stride width, length, height and cadence) and cognitive function (MoCA) score (P<0.05). The largest effect sizes were found for cognitive function scores of RMET [η²=0.716 (95%CI: 0.611~0.761), P<0.05], DSST [η²=0.667 (95%CI: 0.553~0.744), P<0.05], and MoCA [η²=0.597 (95%CI: 0.425~0.750), P<0.05], all of which were classified as medium effect sizes. ② Associative characteristics of motor and psychological factors in the PD-FOG group: H&Y stage was positively correlated with HADS-A [r=0.470 (95%CI: 0.080~0.735), P=0.018] and HADS-D [r=0.560 (95%CI: 0.199~0.787), P=0.004], while the total score of UPDRS-Ⅲ was negatively correlated with DSST [r=-0.574 (95%CI: -0.794~-0.219), P=0.003]. ③Subgroup analysis revealed significant differences (P<0.05) between the TP and SS patterns in motor parameters (stride length and cadence). Moderate effect sizes were observed for HADS-A [δ=0.752 (95%CI: -0.070~1.558), P=0.072], SHAPS [δ=0.512 (95%CI: -0.291~1.305), P=0.132] and HADS-D [δ=0.481 (95%CI: -0.321~1.273), P=0.253], with mean increase by 39.0%, 8.3%, and 24.5%, respectively, in the TP subgroups when compared to the SS subgroups. Conclusion‍　‍PD-FOG patients exhibit characteristic changes in motor function and psychological factors. Cognitive impairment in PD patients may serve as a characteristic marker for FOG progression. Additionally, psychological features in PD-FOG patients with different motor phenotypes show trends of phenotypic heterogeneity.